Genetic investigation and diagnosis in adults with congenital heart disease with or without structural or neurodevelopmental comorbidity: a retrospective chart review - Edwards, Moriah; Zhang, Xue; Opotowsky, Alexander R.; Brown, Nicole; Shikany, Amy R.; Weaver, Kathryn Nicole (Frontiers in Genetics, 2024)
Genetic evaluation is indicated for individuals with congenital heart disease (CHD), especially if extracardiac anomalies are also present. Timely recognition of genetic diagnoses can facilitate medical management and as well as provide assessment of reproductive risk. At least 20% of the pediatric population with CHD has a syndrome or genetic diagnosis. Further, at least 30% have extracardiac congenital malformations and/or neurodevelopmental differences (NDD), and this is known to increase the likelihood of a genetic/syndromic diagnosis. However, little is known regarding whether these statistics also apply to the current population of adults living with CHD, many of whom were born prior to currently available genetic testing. The primary aim of this study was to determine the prevalence of documented genetic and syndromic diagnoses in a cohort of adults with CHD followed by a dedicated adult CHD (ACHD) clinic. The secondary aims were to describe genetic testing and genetic referral patterns in this population and identify the presence of extracardiac comorbidities which are known to be indicative of an underlying genetic diagnosis in the pediatric CHD population. To answer these questions, we performed a retrospective chart review on a sample of adults with CHD (excluding those with isolated bicuspid aortic valve) seen at Cincinnati Children's Hospital in the ACHD clinic between 2010-2021. Among 233 adult CHD patients, 36 (14%) had a documented genetic or syndromic diagnosis but only 29(13.7%) had received genetic testing, while 27(11.6%) had received genetic referrals. Furthermore, of 170 patients without any documented genetics related care (defined as genetic testing, genetic referrals, or genetic diagnosis), 35 (20%) had at least one congenital and/or neurodevelopmental comorbidity. Factors associated with individuals having received genetics related care included younger age (< 40), male sex, and presence of extracardiac comorbidities. Our results indicate important gaps in genetics-related care for adults living with CHD. The subset of our cohort with congenital and/or neurodevelopmental comorbidities who received no genetic-related care, represent a population of adults with CHD who may have unrecognized genetic diagnoses.